Backpropagation


CSE 849: Deep Learning

Vishnu Boddeti

Today

  • Chain Rule
  • Computational Graphs
  • Backpropagation

Overview

  • Given a neural network, our goal is to learn the optimal parameters.
  • Backpropagation is one of the central tool necessary for this purpose.
    • It is an algorithm to efficiently compute gradients.
    • It is an instance of reverse-mode automatic differentiation, a more broadly applicable tool for computing gradients.
    • Salient Features of Backpropagation are:
      • Chain Rule
      • Gradient Caching

Derivatives of Functions

$$ \begin{align} z &= wx + b & y &= \sigma(z) & \mathcal{L} &= \frac{1}{2}(y-t)^2 \nonumber \end{align} $$
  • Compute Derivatives using Calculus:
$$ \begin{eqnarray} \frac{\partial \mathcal{L}}{\partial w} &=& \nonumber \\ &=& \nonumber \\ &=& \nonumber \\ &=& \nonumber \\ &=& \nonumber \end{eqnarray} $$

Derivatives of Functions

$$ \begin{align} z &= wx + b & y &= \sigma(z) & \mathcal{L} &= \frac{1}{2}(y-t)^2 \nonumber \end{align} $$
  • Compute Derivatives using Calculus:
$$ \begin{eqnarray} \frac{\partial \mathcal{L}}{\partial w} &=& \frac{\partial}{\partial w} \left[\frac{1}{2}(\sigma(wx+b)-t)^2\right] \nonumber \\ &=& \frac{1}{2}\frac{\partial}{\partial w} (\sigma(wx+b)-t)^2 \nonumber \\ &=& (\sigma(wx+b)-t)\frac{\partial}{\partial w} (\sigma(wx+b)-t) \nonumber \\ &=& (\sigma(wx+b)-t)\sigma'(wx+b)\frac{\partial}{\partial w} (wx+b) \nonumber \\ &=& (\sigma(wx+b)-t)\sigma'(wx+b)x \nonumber \end{eqnarray} $$

Chain Rule

Univariate Chain Rule

  • Univariate Chain Rule: If $f(x)$ and $x(t)$ are two univariate functions, then
  • $$ \begin{equation} \frac{\partial}{\partial t}f(x(t)) = \frac{\partial f}{\partial x}\frac{\partial x}{\partial t} \end{equation} $$

Univariate Chain Rule Example

  • Forward Pass:
  • $$ \begin{eqnarray} z &=& wx + b \nonumber \\ y &=& \sigma(z) \nonumber \\ \mathcal{L} &=& \frac{1}{2}(y-t)^2 \nonumber \end{eqnarray} $$
  • Computing Derivatives using Chain Rule:
  • $$ \begin{eqnarray} \mathcal{L}' &=& \nonumber \\ y' &=& \nonumber \\ z' &=& \nonumber \\ w' &=& \nonumber \\ b' &=& \nonumber \end{eqnarray} $$

Univariate Chain Rule Example

  • Forward Pass:
  • $$ \begin{eqnarray} z &=& wx + b \nonumber \\ y &=& \sigma(z) \nonumber \\ \mathcal{L} &=& \frac{1}{2}(y-t)^2 \nonumber \end{eqnarray} $$
  • Computing Derivatives using Chain Rule:
  • $$ \begin{eqnarray} \mathcal{L}' &=& 1 \nonumber \\ y' &=& y - t \nonumber \\ z' &=& y'\sigma'(z) \nonumber \\ w' &=& z'x \nonumber \\ b' &=& z' \nonumber \end{eqnarray} $$

Univariate Chain Rule

  • We can represent the computations using a computational graph.
  • Nodes represent all the inputs and computed quantities.
  • Edges represent which nodes are computed directly as a function of which other nodes.

Multivariate Chain Rule

  • Problem: what if the computation graph has a fan-out $> 1$
    • This requires the multivariate Chain Rule.
$L_2$ Regularized Regression

Multivariate Chain Rule

  • Suppose we have a function $f(x,y)$ and functions $x(t)$ and $y(t)$.
  • All the variables here are scalar-valued.
$$ \begin{equation} \frac{d}{dt}f(x(t),y(t)) = \frac{\partial f}{\partial x}\frac{dx}{dt} + \frac{\partial f}{\partial y}\frac{dy}{dt} \end{equation} $$

Multivariate Chain Rule Example

  • Forward Pass:
  • $$ \begin{eqnarray} f(x,y) &=& y + \exp(xy) \nonumber \\ x(t) &=& \cos(t) \nonumber \\ y(t) &=& t^2 \nonumber \end{eqnarray} $$
  • Computing Derivatives:
  • $$ \begin{eqnarray} \frac{\partial f}{\partial t} &=& \nonumber \\ \end{eqnarray} $$

Multivariate Chain Rule Example

  • Forward Pass:
  • $$ \begin{eqnarray} f(x,y) &=& y + \exp(xy) \nonumber \\ x(t) &=& \cos(t) \nonumber \\ y(t) &=& t^2 \nonumber \end{eqnarray} $$
  • Computing Derivatives:
  • $$ \begin{eqnarray} \frac{\partial f}{\partial t} &=& \frac{\partial f}{\partial x}\frac{\partial x}{\partial t} + \frac{\partial f}{\partial y}\frac{\partial y}{\partial t} \nonumber \\ &=& (y\exp(xy))\cdot(-\sin(t)) \nonumber \\ && + (1+x\exp(xy))\cdot(2t) \nonumber \end{eqnarray} $$

Backpropagation

Multivariate Chain Rule

  • In the context of backpropagation:
  • In our notation:
  • $$ \begin{equation} t' = x'\frac{dx}{dt} + y'\frac{dy}{dt} \end{equation} $$

Patterns in Gradient Flow

add gate: gradient distributor
mul gate: gradient distributor

Univariate Backpropagation

  • Example: univariate least squares regression
  • Forward Pass:
$$ \begin{eqnarray} z &=& wx+b \nonumber \\ y &=& \sigma(z) \nonumber \\ \mathcal{L} &=& \frac{1}{2}(y-t)^2 \nonumber \\ \mathcal{R} &=& \frac{1}{2}w^2 \nonumber \\ \mathcal{L}_{reg} &=& \mathcal{L} + \lambda\mathcal{R} \nonumber \end{eqnarray} $$

Multivariate Backpropagation

  • Example: Multilayer Perception (multiple outputs)
  • Forward Pass:
$$ \begin{eqnarray} z_i &=& \sum_{j}w^{(1)}_{ij}x_j + b^{(1)}_i \nonumber \\ h_i &=& \sigma(z_i) \nonumber \\ y_k &=& \sum_{i}w^{(2)}_{ki}h_i+b^{(2)}_k \nonumber \\ \mathcal{L} &=& \frac{1}{2}\sum_k(y_k-t_k)^2 \nonumber \end{eqnarray} $$

Vector Form

  • Computation graphs showing individual units are cumbersome.
  • As you might imagine, we typically draw graphs over vectorized variables.
  • We pass messages back analogous to the ones for scalar-valued nodes.

Vector Form

  • Consider this computation graph:
  • Backprop rules:
  • $$ \begin{equation} z_{j}' = \sum_{k}y_k'\frac{\partial y_k}{\partial z_j} \mbox{ or } \mathbf{z}' = \frac{\partial \mathbf{y}^T}{\partial \mathbf{z}}\mathbf{y}' \end{equation} $$
  • where $\frac{\partial \mathbf{y}}{\partial \mathbf{z}}$ is the Jacobian matrix: $\mathbf{J} = \frac{\partial \mathbf{y}}{\partial \mathbf{x}} = \begin{bmatrix} \frac{\partial y_1}{\partial x_1} & \dots & \frac{\partial y_1}{\partial x_n} \\\ \vdots & \ddots & \vdots \\\ \frac{\partial y_n}{\partial x_1} & \dots & \frac{\partial y_n}{\partial x_n} \end{bmatrix}$

MLP Backpropagation

  • Example: Multilayer Perception (vector form)
  • Forward Pass:
$$ \begin{eqnarray} \mathbf{z} &=& \mathbf{W}^{(1)}\mathbf{x}+\mathbf{b}^{(1)} \nonumber \\ \mathbf{h} &=& \sigma(\mathbf{z}) \nonumber \\ \mathbf{z} &=& \mathbf{W}^{(2)}\mathbf{h}+\mathbf{b}^{(2)} \nonumber \\ \mathcal{L} &=& \frac{1}{2}\|\mathbf{t}-\mathbf{y}\|_2^2 \nonumber \end{eqnarray} $$

Backpropagation Implementation: Modular API


    class ComputationalGraph(object):
      # ...
      def forward(inputs):
        # 1. [pass inputs to input gates]
        # 2. forward the computational graph
        for gate in self.graph_nodes_topologically_sorted():
          gate.forward()
        return loss # final gate in the graph outputs the loss
      def backward(loss):
        for gate in reversed(self.graph_nodes_topologically_sorted()):
          gate.backward() # chain rule applied
        return input_gradients
  

Backpropagation: PyTorch Example

Op: $z = x * y$

    class Multiply(torch.autograd.Function):
      @staticmethod
      def forward(ctx, x, y):
        ctx.save_for_backward(x,y)
        z = x * y
        return z
      @staticmethod
      def backward(ctx, grad_z):
        x, y = ctx.saved_tensors
        grad_x = y * grad_z # dz/dx * dL/dz
        grad_y = x * grad_z # dz/dy * dL/dz
        return grad_x, grad_y
  

Caching Gradients

$$ \begin{equation} \frac{\partial l}{\partial \mathbf{\theta}} = \left[\frac{\partial l}{\mathbf{W}_1},\frac{\partial l}{b_1},\dots,\frac{\partial l}{\mathbf{W}_L},\frac{\partial l}{b_L} \right] \nonumber \end{equation} $$ $$ \begin{eqnarray} f(\mathbf{x}) &=& \mathbf{b}+\mathbf{W}\mathbf{x} \nonumber \\ o(\mathbf{x}) &=& g^L\left(f^L\left(g^{L-1}\left(f^{L-1}\left(\dots\right)\right)\right)\right) \nonumber \end{eqnarray} $$
  • $\frac{\partial l}{\partial W^L_{ij}} = $
  • $\frac{\partial l}{\partial W^{L-1}_{ij}} = $

Caching Gradients

$$ \begin{equation} \frac{\partial l}{\partial \mathbf{\theta}} = \left[\frac{\partial l}{\mathbf{W}_1},\frac{\partial l}{b_1},\dots,\frac{\partial l}{\mathbf{W}_L},\frac{\partial l}{b_L} ]\right] \nonumber \end{equation} $$ $$ \begin{eqnarray} f(\mathbf{x}) &=& \mathbf{b}+\mathbf{W}\mathbf{x} \nonumber \\ o(\mathbf{x}) &=& g^L\left(f^L\left(g^{L-1}\left(f^{L-1}\left(\dots\right)\right)\right)\right) \nonumber \end{eqnarray} $$
  • $\frac{\partial l}{\partial W^L_{ij}} = \frac{\partial l}{\partial o(\mathbf{x})}\frac{\partial o(\mathbf{x})}{\partial g^L}\frac{\partial g^L}{\partial f^L}\frac{\partial f^L}{\partial W^L_{ij}}$
  • $\frac{\partial l}{\partial W^{L-1}_{ij}} = \frac{\partial l}{\partial o(\mathbf{x})}\frac{\partial o(\mathbf{x})}{\partial g^L}\frac{\partial g^L}{\partial f^L}\frac{\partial f^L}{\partial g^{L-1}}\frac{\partial g^{L-1}}{\partial f^{L-1}}\frac{\partial f^{L-1}}{\partial W^{L-1}_{ij}}$

Computational Cost

  • Computational cost of forward pass: one add-multiply operation per weight
  • $$ z_i = \sum_j w^{(1)}_{ij}x_j + b^{(1)}_i $$
  • Computational cost of backward pass: two add-multiply operations per weight
  • $$w^{(2)}_{ki} = y_k' h_i$$ $$h_{i}' = \sum_k y_k' w^{(2)}_{ki}$$
  • Rule of thumb: the backward pass is about as expensive as two forward passes.
  • For a multilayer perceptron, this means the cost is linear in the number of layers, quadratic in the number of units per layer.

Q & A

XKCD

MLP Gradients (Optional)

Recap: Multilayer Neural Network

  • Could have $L$ hidden layers:
    • layer pre-activation for $k>0$ ($\mathbf{h}^{(0)}(\mathbf{x})=\mathbf{x}$)
    • $\mathbf{a}^{(k)}(\mathbf{x}) = \mathbf{b}^{(k)} + \mathbf{W}^{(k)}\mathbf{h}^{(k-1)}(\mathbf{x})$
    • hidden layer activation ($k$ from 1 to $L$):
    • $\mathbf{h}^{(k)}(\mathbf{x}) = \mathbf{g}(\mathbf{a}^{(k)}(\mathbf{x}))$
    • output layer activation ($k=L+1$):
    • $\mathbf{h}^{(L+1)}(\mathbf{x}) = \mathbf{o}(\mathbf{a}^{(L+1)}(\mathbf{x})) = f(\mathbf{x})$

Loss Function

  • Maximum Likelihood Estimate:
  • $$ \mathbf{\theta}^* = \underset{\theta}{\operatorname{arg max}}\prod_i p(y_i=c|\mathbf{x}_i) $$
  • Classification:
  • $$ l = l(\mathbf{x},\mathbf{\theta};y) = \sum_i -\log f(\mathbf{x}_i)_y $$

Output Layer Gradient

  • Partial Derivative:
  • \begin{equation} \frac{\partial}{\partial f(\mathbf{x})_c} -\log f(\mathbf{x})_y = -\frac{1_{y=c}}{f(\mathbf{x})_y} \nonumber \end{equation}
  • Gradient:
  • \begin{eqnarray} && \nabla_{f(\mathbf{x})} -\log f(\mathbf{x})_y \nonumber \\ &=& \frac{-1}{f(\mathbf{x})_y} \begin{bmatrix} 1_{y=0} \\ \vdots \\ 1_{y=C-1} \end{bmatrix} \nonumber \\ &=& \frac{-e(y)}{f(\mathbf{x})_y} \nonumber \end{eqnarray}

Output Layer Gradient Continued...

  • Partial Derivative:
  • $$ \begin{eqnarray} && \frac{\partial}{\partial a^{(L+1)}(\mathbf{x})_c} -\log f(\mathbf{x})_y \nonumber \\ &=& -(1_{y=c}-f(\mathbf{x})_c) \nonumber \end{eqnarray} $$
  • Gradient:
  • \begin{eqnarray} && \nabla_{a^{(L+1)}(\mathbf{x})} -\log f(\mathbf{x})_y \nonumber \\ &=& -(\mathbf{e}(y)-f(\mathbf{x})) \nonumber \end{eqnarray}

Hidden Layer Gradient

  • Partial Derivative:
  • $$ \begin{eqnarray} && \frac{\partial}{\partial h^{(k)}(\mathbf{x})_j}-\log f(\mathbf{x})_y \nonumber \\ &=& \sum_i \frac{\partial-\log f(\mathbf{x})_y}{\partial a^{(k+1)}(\mathbf{x})_i}\frac{\partial a^{(k+1)}(\mathbf{x})_i}{\partial h^{(k)}(\mathbf{x})_j} \nonumber \\ &=& \sum_i \frac{\partial-\log f(\mathbf{x})_y}{\partial a^{(k+1)}(\mathbf{x})_i}W^{k+1}_{i,j} \nonumber \\ &=& \left(\mathbf{W}^{k+1}_{.,j}\right)^T\left(\nabla_{a^{(k+1)}(\mathbf{x})}-\log f(\mathbf{x})_y\right) \nonumber \end{eqnarray} $$

Activation Function Gradient

  • Partial Derivative:
  • $$ \begin{eqnarray} && \frac{\partial}{\partial a^{(k)}(\mathbf{x})_j}-\log f(\mathbf{x})_y \nonumber \\ &=& \frac{\partial -\log f(\mathbf{x})_y}{\partial h^{(k)}(\mathbf{x})_j}\frac{\partial h^{(k)}(\mathbf{x})_j}{\partial a^{(k)}(\mathbf{x})_j} \nonumber \\ &=& \frac{\partial}{\partial h^{(k)}(\mathbf{x})_j}g'\left(a^{(k)}(\mathbf{x})_j\right) \nonumber \\ &=& (\nabla_{h^{(k)}(\mathbf{x})}-\log f(\mathbf{x})_y) \odot [\dots,g'\left(a^{(k)}(\mathbf{x})_j\right),\dots] \nonumber \end{eqnarray} $$

Linear Activation

Sigmoid Activation

Tanh Activation

Rectified Linear Unit Activation

Gradient of Parameters

  • Partial Derivative (weights):
  • $$ \begin{eqnarray} && \frac{\partial}{\partial W^{(k)}_{i,j}}-\log f(\mathbf{x})_y \nonumber \\ &=& \frac{\partial -\log f(\mathbf{x})_y}{\partial a^{(k)}(\mathbf{x})_i}\frac{\partial a^{(k)}(\mathbf{x})_i}{\partial W^{(k)}_{i,j}} \nonumber \\ &=& \frac{\partial -\log f(\mathbf{x})_y}{\partial a^{(k)}(\mathbf{x})_i}h_j^{(k-1)}(\mathbf{x}) \nonumber \\ &=& \left(\nabla_{\mathbf{a}^(k)}(\mathbf{x})-\log f(\mathbf{x})_y\right) \mathbf{h}^{(k-1)}(\mathbf{x})^T \nonumber \end{eqnarray} $$

Gradient of Parameters

  • Partial Derivative (biases):
  • $$ \begin{eqnarray} && \frac{\partial}{\partial b^{(k)}_{i}}-\log f(\mathbf{x})_y \nonumber \\ &=& \frac{\partial -\log f(\mathbf{x})_y}{\partial a^{(k)}(\mathbf{x})_i}\frac{\partial a^{(k)}(\mathbf{x})_i}{\partial b^{(k)}_{i}} \nonumber \\ &=& \frac{\partial -\log f(\mathbf{x})_y}{\partial a^{(k)}(\mathbf{x})_i} \nonumber \\ &=& \left(\nabla_{\mathbf{a}^(k)}(\mathbf{x})-\log f(\mathbf{x})_y\right) \nonumber \end{eqnarray} $$

Backpropagation Algorithm

  • Assuming Forward Propagation is already done.
    • compute output gradient (before activation)
    • $$ \nabla_{\mathbf{a}^{(L+1)}(\mathbf{x})} -\log f(\mathbf{x})_y \Longleftarrow -(\mathbf{e}(y)-\mathbf{f}(\mathbf{x})) $$
    • for $k$ from $L+1$ to 1
      • compute gradients of hidden layer parameter
      • $$ \begin{eqnarray} \nabla_{\mathbf{W}^{(k)}} -\log f(\mathbf{x})_y &\Longleftarrow& (\nabla_{\mathbf{a}^{(k)}} -\log f(\mathbf{x})_y) \mathbf{h}^{(k-1)}(\mathbf{x})^T \nonumber \\ \nabla_{\mathbf{b}^{(k)}} -\log f(\mathbf{x})_y &\Longleftarrow& \nabla_{\mathbf{a}^{(k)}} -\log f(\mathbf{x})_y \nonumber \end{eqnarray} $$
      • compute gradient of hidden layer below
      • $$ \begin{equation} \nabla_{\mathbf{h}^{(k-1)}} -\log f(\mathbf{x})_y \Longleftarrow \mathbf{W}^{(k)^T}\left(\nabla_{\mathbf{a}^{(k)}} -\log f(\mathbf{x})_y\right) \end{equation} $$
      • compute gradient of hidden layer below (before activation)
      • $$ \begin{equation} \nabla_{\mathbf{a}^{(k-1)}} -\log f(\mathbf{x})_y \Longleftarrow \left(\nabla_{\mathbf{h}^{(k-1)}} -\log f(\mathbf{x})_y\right) \odot [\dots,g'(a^{(k-1)}(\mathbf{x})_j),\dots] \nonumber \end{equation} $$

Computational Flow Graph: Forward Pass

  • Forward propagation: represented as an acyclic flow graph
  • Forward propagation: implement in a modular way
    • each box is an object with fprop method, computes value of box given its parents
    • call fprop method of each box in the right order to yield forward propagation

Computational Flow Graph: Backward Pass

  • Each object also has a bprop method
    • computes gradient of loss wrt each child
    • bprop depends on the bprop of the a box's children
  • calling bprop in the reverse order, we get backpropagation